1998
DOI: 10.1021/jp981993e
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fluorescence Studies of Excited Sr Reactions. 1. Sr(3P1) + HF

Abstract: Electronic ground-state SrF (X 2 Σ) products formed in the reaction of electronically excited Sr( 3 P 1 ) with HF are studied using laser-induced fluorescence (LIF) detection. Sr atoms are excited to the 3 P 1 state using a frequency-narrowed and -stabilized linear titanium-sapphire laser at 689.3 nm. The vibrational and rotational population distributions in the SrF(X 2 Σ) products are deduced from the LIF spectra of the B 2 Σ-X 2 Σ and A 2 Π 3/2 -X 2 Σ transitions using spectrum simulation. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…In this transition the R 1 and R 2 branches form bandheads at Nϭ150-90 and N ϭ180-120 for vϭ0 -20, respectively. ͓N is the quantum number belonging to NϭJϪS, where J is the total angular momentum ͑quantum number J͒, and S is the electron spin ͑quantum number Sϭ 1 2 ͒.͔ The rotational population distribution could be determined accurately from the relative intensity of the bandheads for a certain vibrational level. Figure 2 presents the experimental ͑a͒ and simulated ͑b͒ LIF spectrum of SrF formed in the reaction of Sr( 3 P 1 ) with CHFvCH 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this transition the R 1 and R 2 branches form bandheads at Nϭ150-90 and N ϭ180-120 for vϭ0 -20, respectively. ͓N is the quantum number belonging to NϭJϪS, where J is the total angular momentum ͑quantum number J͒, and S is the electron spin ͑quantum number Sϭ 1 2 ͒.͔ The rotational population distribution could be determined accurately from the relative intensity of the bandheads for a certain vibrational level. Figure 2 presents the experimental ͑a͒ and simulated ͑b͒ LIF spectrum of SrF formed in the reaction of Sr( 3 P 1 ) with CHFvCH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A correction factor for saturation by optical pumping is used, as was established in previous experiments. 1 Each rovibronic line intensity is multiplied by, 1/(1Ϫ0.8q v Ј v Љ ), where q v Ј v Љ is the Franck-Condon factor of the vЈ↔vЉ transition, taken from Refs. 18 and 19 for the A 2 ⌸ 3/2 and B 2 ⌺ state, respectively.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ®ndings for Ca HF are consistent with a model in which the Ca atom inserts into the HF bond to form a long-lived H±Ca± F intermediate; the ®ndings for Sr HF are interpreted as competition between direct reaction and reaction which samples the deep H±Sr±F potential well. Chiu-Kwan and Estler [11,12] studied the eect of rotation in the reaction by the experiment. They reported that for each initial rotational level j 1Y 2Y 3, a nearly statistical distribution of SrF product vibrational energy is observed.…”
Section: Introductionmentioning
confidence: 99%
“…We report here the eectiveness of vibrational, translational and rotational excitation on the endothermic reaction Sr HF 3 SrF HY DH 6X4 AE 1X6 kcal/mol [11,12], using QCT method based on the extended London±Eyring±Polanyi±Sato (LEPS) potential energy surface (PES). Because, the reaction is more endothermic than the K HCl reaction [20], one might expect that the energy requirement for Sr HF would be more selective.…”
Section: Introductionmentioning
confidence: 99%